Effect of establishment methods and nitrogen levels on finger millet (Eleusine coracana L Gaertn) - Pradhan, Adikant; Sao, A.; Patel, D.P.; Nag, S.K.; Mukherjee, S.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted during the rainy (Kharif) season 2010 and 2011 at S.G. College of Agriculture and Research Station, Jagdalpur with 6 establishment methods in horizontal plots and 4 nitrogen levels in vertical plots in strip-plot design on sandy -loam soil. Manual transplanted finger millet (Eleusine coracana L. Gaertn) being statistically on par with seed drill sown finger millet with brown manuring, showed significantly higher values of growth and yield attributes. Significantly higher effective tillers/m 2, finger length, grains/finger were recorded under manual transplanting with brown manuring which was statistically at par with seed drill sown finger millet with brown manuring method and seed cum fertilizer sown finger millet during both the years. Manual transplanted finger millet with brown manuring resulted in 10.71, 3.51 and 7.14% higher grain yield over seed drill sown finger millet, conventional practice and manual transplanted finger millet without brown manuring respectively. Manual transplanted finger millet with brown manuring recorded significantly higher N-use efficiency followed by seed drill sown finger millet with brown manuring and manual transplanting with brown manuring. Seed drill sown finger millet gave more net returns than conventional practice, manual transplanted with brown manuring, manual transplanted finger millet without manuring and seed cum fertilizer drill sown finger millet with brown manuring. The plant growth characters, yield attributes, grain and straw yields were significantly higher with application of 125% of recommended dose of nitrogen was recorded. 125% of recommended dose of nitrogen showed significantly higher N-use efficiency with in comparison to all other nitrogen levels. Â